Mediating intimacies through mobile communication: Chinese migrant mothers’ digital ‘bridge of magpies’ - WANG, Yang (Institutional Knowledge at Singapore Management University, 2017)
This chapter introduces a closer investigation of the quotidian routines of mobile communication by Chinese study mothers and their families in their home country, with a particular focus on the contextual constraints that shape their transnational communication practices. It seeks to demonstrate how transnational life situations posed significant constraints on the migrants' expression of intimacies, while also showing that the migrants could be highly creative in circumventing these contextual limitations. Similar to the romantic Chinese legend of the weaver girl and the cowherd who reunite only once a year on a bridge formed by magpies, transnational families who are separated by insurmountable geographical distance also 'meet' each other on the digital 'bridge of magpies' forged by information and communication technologies. In technology-mediated spaces, transnational family members can remain involved in one another's mundane experiences and perform familial responsibilities from afar on a daily basis, thus reconstituting family intimacies across national borders.